Transitions écologique et numérique : quelle régulation du sens par la Commission européenne ? - Marie-Hélène Hermand (Communiquer)
This article questions how the European Commission (EC) is making a case for the ecological and digital transition, two strategic priorities for 2019-2024 that are difficult to reconcile and coexist. As intimately linked in substance as they are separate in form, the ecological and digital transitions are the subject of two distinct sections on the EC web portal: they constitute the corpus of the study, multimodal and rich from an editorial point of view. After having situated our approach within the theoretical approaches of European public communication and elaborated the methodology according to a discursive and semiotic approach, we confront the results of the discourse analysis with those of the study of textual landscapes. The discursive filiations, tensions, variants (motifs, narratives and proposed models; significant places and moments), and invariants (gnomic statements) identified allow us to specify the Doxa on which the communicational paradox considered is based.